Utilization of Maintenance and Other Operating Expenses (MOOE) in Relation to Students’ Academic Performance - Comighud, Sheena Mae T.; Arevalo, Limer N. (International Journal For Research In Educational Studies, 2020)
This research used the descriptive method to determine the extent of utilization of Maintenance and Other Operating Expenses (MOOE) in relation to Students’ Academic Performance in the Public Elementary Schools of Bayawan City Division, Negros Oriental for SY 2018-2019. The quantitative data were gathered from 68 teachers’ league presidents and 68 school heads. Also, the researcher conducted a survey questionnaire. Descriptive method was used in this study. The statistical tools used in the analysis of the data were percentage, mean, weighted mean, and spearman rank correlation coefficient. The study found out that the extent of utilization of the Maintenance and Other Operating Expenses (MOOE) as perceived by the teachers’ league presidents and school heads was “high” in terms of the following aspects: (a) school operations and development; (b) teachers’ welfare and development and (c) students’ welfare and development. In addition, it was also found out that the level of students’ academic performance is at a “very satisfactory” level. Lastly, findings revealed that there is a significant relationship between the extent of utilization of the Maintenance and Other Operating Expenses (MOOE) and students’ academic performance.